Assessment of Selection Criteria for Low-Dose Lung Screening CT Among Asian Ethnic Groups in Taiwan: From Mass Screening to Specific Risk-Based Screening for Non-Smoker Lung Cancer - Wu, Fu-Zong; Huang, Yi-Luan; Wu, Carol C.; Tang, En-Kuei; Chen, Chi-Shen; Mar, Guang-Yuan; Yen, Yu; Wu, Ming-Ting (Clinical lung cancer, 2016)
We aim to investigate the impact of applying the NLST eligibility criteria to the population in Taiwan, and to identify additional risk factors to select subjects at risk of lung cancer. Our findings suggest that female gender and a family history of lung cancer are two important predictor. A prospective study design based on survival analysis in non-smoker lung cancer screening is warranted. The National Lung Screening Trial (NLST) showed low-dose screening chest computed tomography (CT) reduced the lung cancer mortality rate up to 20% in high-risk patients in the United States. We aimed to investigate the impact of applying the NLST eligibility criteria to the population in Taiwan, and to identify additional risk factors to select subjects at risk for lung cancer. We retrospectively reviewed the medical records of 1763 asymptomatic healthy subjects (age range, 40-80 years) who voluntarily underwent low-dose chest CT (1029 male, 734 female) from August 2013 to August 2014. Clinical information and nodule characteristics were recorded. The results of subsequent follow-up and outcome were also recorded. A total of 8.4% (148/1763) of subjects would have been eligible for lung cancer screening based on the NLST criteria. However, only 1 of these eligible subjects would have a lung cancer detected at baseline. Among the 1615 subjects who did not meet the NLST criteria, the detection rates of lung cancer were 2.6% in women and 0.56% in men. Logistic regression showed that female gender and a family history of lung cancer were the 2 most important predictors of lung cancer in Taiwan (odds ratio, 6.367; P = .003; odds ratio, 3.017; P = .016, respectively). In conclusion, NLST eligibility criteria may not be effective in screening for lung cancer in Taiwan. A risk-based prediction model based on the family history of lung cancer and female gender can potentially improve the efficiency of lung cancer screening programs in Taiwan.